Simulations and Comparisons of Channeling Spectra in the p+28Si System in the Backscattering Geometry - Kokkoris, M.; Aslanoglou, X. A.; Karydas, A.; Kossionides, E.; Paradellis, Th.; Souliotis, G.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
A new method has recently been proposed for the simulation and analysis of channeling spectra in the backscattering geometry [1], based on reaction cross sections and the assumption that beam particles escape from the aligned direction at an exponential rate. The success of the method in the system p+28Si cut along the <100> plane [2] led to the investigation of more complicated crystal structures and beam-target combinations, namely a+MgO and a+A^Oa, which revealed the prospects as well as the limitations of the method [3]. In the present work channeling spectra of protons in a 28Si crystal cut along the <111> plane, in the energy region Ep = 1.7-2.4 MeV are studied and analyzed. The measured backscattering spectra are reproduced by computer simulations and an attempt is made to describe the differences between the <100> and the <111> axis in the silicon crystal and their subsequent effect on the stopping power of channeled protons. The results are compared with those of methods reported in the past at different energy regions of the incoming protons [4,5].